The Impact of Brexit on the Security of the Visegrad Group Countries – a Neorealist Perspective (Economic and Political Thought, 2023)
The aim of the article is to analyze the impact of Britain’s exit from the European Union on the security of the Visegrad Group countries. The analysis was made using the neorealist theory. The conclusions of the considerations boil down to the conundrum that Brexit has not directly affected the security of the Visegrad Group countries, but it has changed their thinking about security policy and created regional and global risks associated with a change in the balance of power by weakening the EU as an international organization.
Keywords: brexit, United Kingdom, European Union, Visegrad Group, neorealism, security